STRATEGI PENGEMBANGAN WISATA SERIBU MUSAMUS BERBASIS KEARIFAN LOKAL DI KABUPATEN MERAUKE - Roisyah Budiati; Umar Yampap; Yonarlianto Tembang; Raudya Setya Wismoko Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The strategy of developing tourism based on local wisdom is carried out as an effort to preserve culture. The purpose of this study is to determine the supporting and inhibiting factors of tourism development and to analyze the strategy of developing the Thousand Musamus tourism based on local wisdom. This type of research is qualitative with descriptive methods and purposive sampling techniques. Data collection methods are observation, interviews, and questionnaires. The results of the study show that supporting factors include collaboration with the village community, facility development, promotion, and the formation of Pokdarwis. Inhibiting factors include a large amount of waste, damaged road access, and the risk of land fires during the dry season. The strategy of developing tourism based on local wisdom includes the development of traditional dances, craft products, sago processing, and holding cultural festivals. Road repairs, the availability of additional Bevak, the involvement of local communities in collaboration with Indigenous Peoples Institutions, Village-Owned Enterprises, and the Tourism Office, as well as training for promotion, by integrating local wisdom values ​​into the strategy of developing the Thousand Musamus tourism are expected to make this tourism the most popular tourist attraction in Merauke Regency.